Uji Kualitatif dan Penetapan Kadar dengan Metode Spiking pada Logam Pb di Dalam Minuman Kopi Kaleng - Husnafa Patriani; Fajar Nugraha; Hadi Kurniawan (Journal Syifa Sciences and Clinical Research, 2023)
Lead (Pb) is a heavy metal that is naturally present in the earth’s crust. This metal is dispersed in nature in small amounts through natural processes. Lead that accumulates in the environment is not biodegradable and its toxicity does not change. Contamination of lead (Pb) meta; in canned drinks can occur due to imperfect packaging, damage or rust. Lead metal is obtained from soldering tools. This study aims to identify the presence of Pb metal in canned coffee drinks. In addition, to find out the method of preparation that was carried out correctly the spiking method was used. Samples were taken in Pontianak City with purposive sampling technique. The sample of this research is canned coffee drinks with 3 different brands (brands A, B and C) circulating in the city of Pontianak. The qualitative test was carried out using 0.5 N KI reagent and 2 M HCl which was dropped into the sample. A positive result on a sample that was dripped with 0.5 N KI reagent was a yellow precipitate, while a positive result on a sample that was dripped with 2 M HCl reagent was a white precipitate. The spiking method was carried out by adding 0.3 mL of 1000 ppm Pb standard solution and adding the sample to a volume of 2 mL. Then, wet digestion was carried out using 10 mL HNO3 and 2 mL H2O2 as solvent. The results of the qualitative test showed that all samples with 0.5 N KI reagent were clear and black precipitate formed. All samples that were dropped with 2 M HCl reagent were clear and no precipitate was formed. In assay by spiking method, the levels obtained are 73.54 mg/kg and % recovery is 86.667%. All tested samples did not contain Pb metal and the preparation method used was correct.